Cybersecurity as the Foundation for the Development of Mobile Financial Applications: A Literature Study on Cybercrime and Its Mitigation - Jamil, Shabrun; Irawan, Chandra Purna; Deliysa, Deliysa (Jurnal Ekonomi, Manajemen, dan Bisnis, 2023)
This study examines the importance of cybersecurity in mobile financial applications, particularly in the face of rising  cybercrime  threats.  The  aim  of  this  research  is  to  provide  deeper  insights  into  the  significance  of cybersecurity in mobile financial apps and to develop approaches that financial companies can adopt to protect their  users'  data  and  information.  The  research  employs  a  qualitative  descriptive  method  using  a  systematic literature review (SLR) approach. Meta-synthesis analysis is applied to synthesize data from 26 journal articles published between 2019 and 2024. The findings reveal that cybercrime in the financial and FinTech industries is driven  by  internal  factors  such  as  weak  security  systems,  lack  of  system  updates,  limited  human  resource competencies, and careless user behavior. External factors include malware attacks, unclear regulations, and the use  of  advanced technology.  To  counter  these, it is  necessary  to  implement technologies  such  as firewalls  and blockchain, strong risk management, enhanced network infrastructure, the establishment of cybersecurity teams, the  development  of  clear  regulations,  and  user  education  to  raise  awareness  and  improve  cybersecurity. Therefore, the implementation of a comprehensive cybersecurity strategy is crucial in maintaining the integrity and trust of users in mobile financial applications